The relationship between body mass index and 10-year trajectories of physical functioning in middle-aged and older Russians: Prospective results of the Russian HAPIEE study - Hu, Y; Malyutina, S; Pikhart, H; Peasey, A; Holmes, M; Hubacek, J; Denisova, D; Nikitin, Y; Bobak, M (Springer Paris, 2016)
Objective: To investigate the associations of overweight and obesity with longitudinal decline in physical functioning (PF) among middle-aged and older Russians. Design: Prospective cohort study. Setting: Four rounds of data collection in the Russian Health, Alcohol and Psychosocial factors In Eastern Europe study with up to 10 years of follow-up. Participants: 9,222 men and women aged 45-69 years randomly selected from the population of two districts of Novosibirsk, Russia. Measurements: PF score (range 0-100) was measured by the Physical Functioning Subscale (PF-10) of the 36-item Short Form Health Survey (SF-36) at baseline and three subsequent occasions. Body mass index (BMI), derived from objectively measured body height and weight at baseline, was classified into normal weight (BMI 18.5-24.9), overweight (BMI 25.0-29.9), obesity class I (BMI 30.0-34.9), and obesity class II+ (BMI≥35.0). Results: The mean annual decline in the PF score during the follow-up was -1.92 (95% confidence interval -2.17; -1.68) in men and -1.91 (-2.13; -1.68) in women. At baseline, compared with normal weight, obesity classes I and II+ (but not overweight) were associated with significantly lower PF in both sexes. In prospective analyses, the decline in PF was faster in overweight men (difference from normal weight subjects -0.38 [-0.63; -0.14]), class I obese men and women (-0.49 [-0.82; -0.17] and -0.44 [-0.73; -0.15] respectively) and class II+ obese men and women (-1.13 [-1.73; -0.53] and -0.43 [-0.77; -0.09] respectively). Adjustment for physical activity and other covariates did not materially change the results. Conclusion: PF decreased more rapidly in obese men and women than among those with normal weight. The adverse effect of high BMI on PF trajectories appeared to be more pronounced in men than in women, making more extremely obese Russian men an important target population to prevent/slow down the process of decline in PF.